Application of minimally invasive surgery in tooth extraction procedures: Evaluation of effectiveness and advantages, literature review (Research, Society and Development, 2024)
Objective: To explore the development and application of minimally invasive oral surgery (MIS) as a discipline that seeks to reduce trauma and improve efficiency in dental surgical procedures. It begins by presenting the historical context, highlighting the use of computed tomography and planning software for guided surgery. It then defines MIS and highlights its advantages over traditional surgery, such as shorter recovery times and lower morbidity. Materials and Methods: Search and selection of relevant literature, focusing on systematic reviews, case reports and randomized controlled clinical trials. Thirty articles were identified that met the inclusion criteria (MEDLINE (PubMed), Embase, Sopes and Google Scholar). Results: The various techniques and technologies used in MIS, such as 3D preoperative planning, computer-guided surgery, the use of cone beam computed tomography (CBCT) and artificial intelligence (AI)-assisted image analysis, stand out. In addition, specific intraoperative techniques such as piezosurgery and vertical extraction by pulley action are mentioned, as well as the importance of preoperative planning, the role of technology in improving surgical procedures, and the benefits of minimally invasive techniques in terms of procedural success and patient recovery.